2020
DOI: 10.1007/s13595-020-00999-1
|View full text |Cite|
|
Sign up to set email alerts
|

Improving aboveground biomass estimates by taking into account density variations between tree components

Abstract: Key message Strong density differences were observed between stem wood at 1.30 m and other tree components (stem wood, stem bark, knots, branch stumps and branches). The difference, up to 40% depending on the component, should be taken into account when estimating the biomass available for industrial uses, mainly fuelwood and wood for chemistry.• Context Basic density is a major variable in the calculation of tree biomass. However, it is usually measured on stem wood only and at breast height.• Aims The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…However, our research found that the proportion of root biomass increased with increasing age and then decreased gradually after the trees matured. Generally, the part below the ground from the cutting place is treated as roots, so the root usually contains part of the stem, and the root has more knots and higher density [61], which may be the reason why the proportion of root biomass increases with age.…”
Section: Discussionmentioning
confidence: 99%
“…However, our research found that the proportion of root biomass increased with increasing age and then decreased gradually after the trees matured. Generally, the part below the ground from the cutting place is treated as roots, so the root usually contains part of the stem, and the root has more knots and higher density [61], which may be the reason why the proportion of root biomass increases with age.…”
Section: Discussionmentioning
confidence: 99%
“…However, economic improvement can only occur if the selling price remains the same and the cost advantage will not be passed on to RCF. It also must be noted that a change in wood characteristics could affect carbon efficiency (Billard et al, 2020) that consequently has an impact on the cost. Hence, the decision-maker is advised to carefully assess the potential trade-offs between the cost and carbon efficiency reduction.…”
Section: Interaction Between Costs and Cost Growth Ratementioning
confidence: 99%
“…Vertical variation along the stem must be considered when estimating forest biomass because not considering this source of systematic bias results in significant errors in estimates for vast areas, such as the Amazon [3,17,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%